Demolition and reuse of concrete and masonry : guidelines for demolition and reuse of concrete and masonry : proceedings of the Third International RILEM Symposium on Demolition and Reuse of Concrete and Masonry held in Odense, Denmark, organized by RILEM TC 121-DRG and the Danish Building Research Institute, Odense, Denmark 24-27 October 1993 /: guidelines for demolition and reuse of concrete and masonry : proceedings of the Third International RILEM Symposium on Demolition and Reuse of Concrete and Masonry held in Odense, Denmark, organized by RILEM TC 121-DRG and the Danish Building Research Institute, Odense, Denmark 24-27 October 1993. ([2014?]) - Unknown
No abstract available